Around Particular Existence, Independence and Necessity: Some remarks in the perspective of biological monadism by Stanisław Ignacy Witkiewicz - Kmiecikowski, Waldemar (Filozofia Chrześcijańska, 2023)
The aim of this article is to present the issue of independence and necessity in the philosophical refl ection of Stanisław Ignacy Witkiewicz, which is a constant component of the system created by this thinker. Accordingly, an analysis of selected representative writings of Witkiewicz has been undertaken. The result of the considerations contained in the article is the postulation of a discussion on the subject of the (excluded) Necessary Being and the Mystery of Existence.